2019
DOI: 10.18535/ijsrm/v7i11.em01
|View full text |Cite
|
Sign up to set email alerts
|

Soil Acidity and its Management Options in Ethiopia: A Review

Abstract: Soil acidity is one of the chemical soil degradation problems which affect soil productivity in the Ethiopian highlands. This paper tries to put together soil acidity concept, causes, extent and management practices. Soil acidity is the problem of agricultural activities in Ethiopian highlands (cultivated lands) and is getting an increase. Farmers require simple and sustainable techniques to amend acid soils and improve yields of crops of their choices. Recommendations on reclamation of acid soils need to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In a country where less than 5% of the total cultivated land is irrigated [65], any spatial and temporal changes to this balance between temperature and rainfall are likely to have significant impacts on agricultural production. In this study, we confirm the link between rainfall and soil pH in Ethiopia, where soils in the high-rainfall areas are acidic, while those in the low-rainfall areas tend to be alkaline [19,35]. The highly acidic soils are the nitisols, alisols, and fluvisols, which encompass some of the most intensive crop production areas in Ethiopia [66].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In a country where less than 5% of the total cultivated land is irrigated [65], any spatial and temporal changes to this balance between temperature and rainfall are likely to have significant impacts on agricultural production. In this study, we confirm the link between rainfall and soil pH in Ethiopia, where soils in the high-rainfall areas are acidic, while those in the low-rainfall areas tend to be alkaline [19,35]. The highly acidic soils are the nitisols, alisols, and fluvisols, which encompass some of the most intensive crop production areas in Ethiopia [66].…”
Section: Discussionsupporting
confidence: 71%
“…To emulate the impacts of acidification on crop suitability, we ran the suitability model with current soil pH values (baseline, bl), and then, we acidified the soil by reducing the soil pH by 0.5 (bl-0.5), 1.0 (bl-1.0) and 1.5 (bl-1.5) while the future climatic data remained the same. These values were selected to encompass the observed ranges of soil acidification over recent decades, arising from a combination of natural processes and anthropogenic factors, such as the suboptimal utilization of inorganic fertilizers [24,35,60]. By combining the rainfall and temperature data with each soil acidity level, we conducted a crop suitability analysis for future climate scenarios (i.e., 2050).…”
Section: Assessing Impacts Of Soil Acidification On Crop Suitability ...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Lahav and Israeli (2019) and Soto (2015) observed that K deficiencies in the soil can cause weight loss in banana bunches, specifically affecting the length and diameter of the fingers. For ranges of 6 < pH ≤ 7.3, there is adequate availability of most minerals (Jaramillo, 2014;Golla, 2019) causes, extent and management practices. Soil acidity is the problem of agricultural activities in Ethiopian highlands (cultivated lands, which may indicate good plant nutrition and consequently higher cluster weights.…”
Section: Resultsmentioning
confidence: 99%
“…The soils in the three experimental environments are slightly acidic. The pH ranges for the soil across three experimental sites will still permissible for plant nutrients uptake [23]. The textural class of the soil at the three environments was sandy loam.…”
Section: Soil Properties Of Experimental Sitesmentioning
confidence: 96%